Pengaruh Integritas Dan Profesionalisme Pemeriksa Terhadap Kualitas Pemeriksaan Pajak - MUH TRI SULTAN AL SYAHBAN (P3M STIEM BONGAYA, 2021)
This study aims to determine the effect of integrity and professionalism of auditors on the quality of tax audits (Studies at the South Makassar Tax Office) as many as 100 people, with sample selection techniques using the sovin formula. The analytical method used is multiple linear analysis. The results of this study indicate that the variables of the influence of integrity and professionalism of examiners have a positive and significant effect on the quality of tax audits (Studies at the South Makassar Pratama Tax Office)”